2011
DOI: 10.1063/1.3628459
|View full text |Cite
|
Sign up to set email alerts
|

Misfit dislocation formation via pre-existing threading dislocation glide in (112¯2) semipolar heteroepitaxy

Abstract: Cathodoluminescence (CL) was used to study the onset of mechanical stress relaxation in low indium composition semipolar (112¯2) InxGa1−xN lattice-mismatched layers grown on bulk GaN substrates. Monochromatic CL of short interfacial misfit dislocation (MD) segments showed a single threading dislocation (TD) associated with each MD segment—demonstrating that the initial stage of MD formation in semipolar III-nitride heterostructures proceeded by the bending and glide of pre-existing TDs on the (0001) slip plane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 17 publications
3
81
0
Order By: Relevance
“…6(a)). The dark stripes observed in the I PL maps of both samples can be attributed to misfit dislocations either under the QW active region or under the 100-nm-thick n-In 0.01 Ga 0.99 N layer (as the layer thickness is close to the critical thickness 51 ). It should be noted that the PSS-GaN template also shows such dark stripes.…”
Section: B Optical Propertiesmentioning
confidence: 99%
“…6(a)). The dark stripes observed in the I PL maps of both samples can be attributed to misfit dislocations either under the QW active region or under the 100-nm-thick n-In 0.01 Ga 0.99 N layer (as the layer thickness is close to the critical thickness 51 ). It should be noted that the PSS-GaN template also shows such dark stripes.…”
Section: B Optical Propertiesmentioning
confidence: 99%
“…In our model, the current spreading is connected only with polarization changes. Hsu et al [16] have reported formation of misfit dislocations (MDs) in (1122) InGaN layers grown on GaN substrates due to stress relaxation, however, they have concluded that similar mechanisms for MDs formation have been expected for other semi-polar orientations. Besides, (1122) oriented films appear to be mostly smooth [9].…”
Section: Designing Of Nitride Leds With Reduced Polarization Effectsmentioning
confidence: 99%
“…13 However, the formation of misfit dislocations (MDs) within the active region has been observed and is known to degrade the device performance. 14 The semipolar ð20 21Þ plane, which is miscut by 15 toward c-plane from m-plane, has been utilized to produce highperformance green LEDs (Refs. 15 and 16) and LDs.…”
mentioning
confidence: 99%
“…However, under lower growth temperatures (840 to 880 C), the ð11 22Þ samples were stress relaxed via formation of basal plane MDs at the heterointerfaces. 14 The indium composition of stress relaxed samples were estimated using symmetric reciprocal space maps with the x-ray beam oriented along the c-azimuth. 24 The defected ð11 22Þ samples were estimated to have lower indium compositions compared to the coherent ð20 2 1Þ samples, but the effect of stress relaxation and related defects on the indium incorporation is not yet clear and is a topic of ongoing investigation.…”
mentioning
confidence: 99%